Lessons Learned From the Recruitment of Undocumented African Immigrant Women for a Qualitative Study. (4th February 2020) - Olukotun, Oluwatoyin; Mkandawire-Valhmu, Lucy
Although undocumented immigrants represent a particularly vulnerable population, they are underrepresented in health research. To facilitate the engagement of undocumented immigrants in health research, in this article, we describe the methodological issues encountered while conducting a qualitative study where we sought to understand the health care–seeking experiences of undocumented African immigrant women in the United States. Strategies employed in addressing methodological challenges and recommendation for future studies will also be discussed.